Answer:
(1) x=15/2
(2) x=1
Explanation:
(1) 4x−1 /2 =x+7
2x+ −1 /2 =x+7(Distribute)
2x+ −1 /2 =x+7
Step 2: Subtract x from both sides.
2x+ −1 /2 −x=x+7−x
x+ −1 /2 =7
Step 3: Add 1/2 to both sides.
x+ −1 /2 + 1 /2 =7+ 1 /2
x= 15 /2
(2) 3x+2=( 2x+13)/ 3
3x+2= 2 /3 x+ 13 /3 (Distribute)
3x+2= 2 /3 x+ 13 /3
Step 2: Subtract 2/3x from both sides.
3x+2− 2 /3 x= 2 /3 x+ 13 /3 − 2 /3 x
7 /3 x+2= 13 /3
Step 3: Subtract 2 from both sides.
7 /3 x+2−2= 13 /3 −2
7 /3 x= 7 /3
Step 4: Multiply both sides by 3/7.
( 3 /7 )*( 7 /3 x)=( 3 /7 )*( 7 /3 )
X=1